Exile from Argentina : a Jewish family and the military dictatorship (1976-1983) - Faingold, Eduardo D. (Emerald Publishing Limited : Information Age Publishing, Inc., 2023)
Eduardo Faingold chronicles his family's experiences before, during, and after the military dictatorship in Argentina (1976-1983). He uses his diaries, interviews in Latin America and Israel, documents and pictures given to him by his family and friends and studies the works of political scientists, historians and journalists. He begins with his family history from the time when his ancestors immigrated in the 19th century from Byelorussia and Bessarabia to Argentina as a part of the Baron de Hirsch's emigrant wave that established farming villages in the provinces of Santa Fe and Buenos Aires. Then, using his family's history as background, he discusses his life as an exile in Israel and Denmark from 1976 to 1979, his return to Argentina to comply with his military service in the Argentine Marine Infantry and his return to Israel in 1980.In a revealing preface to the second edition of Exile from Argentina, the author updates the family history and notes some important political events in Argentina and Israel in the 1980s and beyond that help contextualize the author's experiences. Notably, as the author points out in this new preface to Exile from Argentina, by the end of the first quarter of the 21st century, all his siblings and their families, as well as his mother, the descendants of his ancestors who emigrated to Argentina from Byelorussia and Bessarabia at the turn of the 19th century to escape the violence of the Russian pogroms, are now scattered in five continents, living their lives in cultures as varied as those of the United States, Brazil, Israel, Norway, Sweden, and Australia. Finally, this new edition of Exile from Argentina features a trove of historical photos and documents of the author and his family which were not included in the first edition of the book.
"First published in Argentina under the title Diáspora y exilio. Crónica de una familia argentina by Ediciones Al Margen, 2006. Translated by Renata Madinger, Noam Faingold, and Eduardo D. Faingold"--title page verso.
Keywords: Faingold, Eduardo D.; Faingold family.; Faingold, Eduardo D. -- Family.; Jews -- Argentina -- Biography.; Exiles -- Argentina.; Argentina -- History -- Dirty War, 1976-1983 -- Personal narratives.; elektronické knihy; Biographies.; Personal narratives.; Biography & Autobiography -- Jewish.; Autobiography: historical, political and military.; Biography: general.; Relating to Jewish people and groups.; electronic books